In situ synthesis and properties of Ag/Ag10Si4O13/GO photocatalysts with synergistic effect of plasma Resonance and Schottky junction. Issue 3 (16th January 2023) - Li, Cuixia; Zhang, Ruilin; Zhang, Youyou; Jin, Haize; Zhang, Yuhang; Li, Wensheng
Abstract : A novel synthetic strategy for fabricating Ag/Ag10 Si4 O13 /GO Photocatalysts with Synergistic Effect of Plasma Resonance and Schottky Junction was proposed by accurately molecular (ion) scale assembly based on sol–gel method. Abstract : Ongoing studies on photocatalysts based on the response of the overall band spectrum of visible light to clean water resources have received significant attention. This study focuses on the synergistic effect of plasma resonance and Schottky junction of silver as a promoter in Ag10 Si4 O13 /GO-based photocatalysts for improving the photocatalytic performance and stability. The nanostructured Ag/Ag10 Si4 O13 /GO composites were synthesized by an accurate molecular (ion) scale assembly based on the sol–gel method. The response range of visible light was extended to 660 nm, and the combined effect of the Schottky junction and internal polarization electric field of Ag10 Si4 O13 showed excellent charge separation efficiency. The highly efficient non-selective degradation for cationic and anionic dyes was demonstrated under visible light, and methylene blue (20 g mL −1 ) can be completely degraded in 15 min. The excellent cycling stability was obtained due to the inhibition of photoreduction. The novel nano-engineering strategy provided a new reference for highly active photocatalysts.